Complications during chest tube drainage for iatrogenic pneumothorax - Birgitte Siem Joensen; Uffe Bodtger; Christian B. Laursen; Rob J Hallifax; Beenish Iqbal; Søren Helbo Skaarup (European Clinical Respiratory Journal)
Background Iatrogenic pneumothorax is a common complication of diagnostic and therapeutic pulmonary procedures. New guidelines on primary spontaneous pneumothorax suggest ambulatory approaches may be suitable. However, guidance on iatrogenic pneumothorax occurring in patients with impaired lung function, increased age, comorbidity and frailty is lacking, and the safety profile of ambulatory management is not known. The objective was to study the safety of iatrogenic pneumothorax treated with chest tubes and to identify the risks of life-threatening events.Methods In a retrospective cohort of patients admitted and treated with an adhesive valve-integrated chest tube system, we recorded the incidence of complications. The primary outcome was the incidence of life-threatening events that required urgent medical action. Incidences of serious adverse events, adverse events, serious device-related events and whether outpatient ambulatory treatment would be safe were recorded based on the review of the medical charts.Results In 97 patients, 6 (6%) life-threatening events occurred, including episodes of respiratory failure and an urgent need for new chest tube insertion. The event incidence was 21% in patients with pre-biopsy saturation below 95% and 1% in patients with saturation above 95%, p = 0.003, and greater if the lung had not expanded on the first radiograph, 25%, after insertion of the chest tube, than if the lung had fully expanded, 4%, or partially expanded, 2%, p = 0.009.Conclusions The incidence of life-threatening events during chest tube-treated iatrogenic pneumothorax is significant, but acceptable in patients without impaired lung function prior to the procedure and early response to treatment.